2013
DOI: 10.1080/15332691.2013.749681
|View full text |Cite
|
Sign up to set email alerts
|

Professional and Personal Experiences and Perceived Facilitator Effectiveness

Abstract: This study analyzes the relationship between facilitator effectiveness ratings and several facilitator characteristics. Characteristics include professional and personal experiences as well as demographics. Participants attended Smart Steps, a relationship education course for stepfamilies, which was offered through community agencies. There were 858 participants with an overrepresentation of low-income and Latino participants. Facilitators who had specific training in Smart Steps and facilitators who had step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The CRE field has a modest record of examining pedagogical and programmatic processes that facilitate positive change in outcomes (Allgood & Higginbotham, ; Bradford, Adler‐Baeder, Ketring, & Smith, ; Carlson, Barden, Daire, & Swartz, ; Higginbotham & Myler, ; Owen, Antle, & Barbee, ; Owen, Rhoades, Stanley, & Markman, ; Quirk, Owen, Inch, France, & Bergen, ). Also, several studies have found that program effects are moderated by baseline levels of individual and dyadic risk and distress, with greater risk and distress generally predicting greater improvement in intervention outcomes (Allen, Rhoades, Stanley, Loew, & Markman, ; Amato, ; Barton, Futris, & Bradley, ; Bodenmann, Hilpert, Nussbeck, & Bradbury, ; Carlson, Rappleyea, Daire, Harris, & Liu, ; DuPree, Whiting, & Harris, ; Epstein et al, ; Halford et al, ; Halford, Sanders, & Behrens, ; Hawkins & Erickson, ; McGill et al, ; Quirk, Strokoff, Owen, France, & Bergen, ; Schilling, Baucom, Burnett, Allen, & Ragland, ; Williamson et al, ).…”
mentioning
confidence: 99%
“…The CRE field has a modest record of examining pedagogical and programmatic processes that facilitate positive change in outcomes (Allgood & Higginbotham, ; Bradford, Adler‐Baeder, Ketring, & Smith, ; Carlson, Barden, Daire, & Swartz, ; Higginbotham & Myler, ; Owen, Antle, & Barbee, ; Owen, Rhoades, Stanley, & Markman, ; Quirk, Owen, Inch, France, & Bergen, ). Also, several studies have found that program effects are moderated by baseline levels of individual and dyadic risk and distress, with greater risk and distress generally predicting greater improvement in intervention outcomes (Allen, Rhoades, Stanley, Loew, & Markman, ; Amato, ; Barton, Futris, & Bradley, ; Bodenmann, Hilpert, Nussbeck, & Bradbury, ; Carlson, Rappleyea, Daire, Harris, & Liu, ; DuPree, Whiting, & Harris, ; Epstein et al, ; Halford et al, ; Halford, Sanders, & Behrens, ; Hawkins & Erickson, ; McGill et al, ; Quirk, Strokoff, Owen, France, & Bergen, ; Schilling, Baucom, Burnett, Allen, & Ragland, ; Williamson et al, ).…”
mentioning
confidence: 99%